Mixed ion-polaron transport in lithium vanadium-molybdenum tellurite glasses - Montani, Ruben Alfredo (2006)
The electrical properties of mixed ion-polaron conducting vanadium tellurite glasses of the form XLi2O·(1 - X)[0.5V2O5·0.5MoO3]2TeO2 have been studied by using the impedance spectroscopy in a wide range of temperature and composition. The obtained results confirm the existence of a transition from a typically electronic (polaronic) conductive regime when the molar fraction (X) of Li2O is equal to 0, to an ionic conductive regime when X tends to 1. This transition is characterised by a deep minimum in the electrical conductivity of about 3 orders of magnitude. The correlated behaviour between conductivity and the mean distance between lithium ions and between vanadium ions reinforces the key idea of two independent migrating paths for both electrons and ions, respectively.